A comparative analysis of dementia strategies of seventeen European Countries in the context of Glasgow Declaration and WHO’s Global Action Plan - Smruti Bulsari; Nureen Izyani Hashim; Kiran Pandya; Russell Kabir (PLoS ONE, 2025)
Dementia prevalence across the globe is in alarming proportion and it is even expected to rise in the future. The World Health Organisation (WHO) had declared dementia as a health priority, way back in 2009 and had recommended then, that at least high-income countries develop a dementia action plan, and other countries develop a national dementia strategy (NDS). Later in 2014, European Countries came together to sign the Glasgow Declaration and agreed to develop their respective NDSs. Yet, a few countries still do not have their NDS. Moreover, some countries do not have their NDS in English. This study attempts to compare the dementia strategies of 17 European countries, which has a comprehensive NDS in English language. The study further examines how well these NDSs comply with the Glasgow Declaration and the WHO’s Global Action Plan guidance. Cluster analysis is undertaken to classify NDSs of these countries in terms of similarity in the content. Word clouds are used to get an overall idea about the clusterwise contents of the NDSs, and then an algorithmic approach to content analysis is applied for identifying the clusterwise key focus areas of these dementia strategies. A comparative analysis of these NDSs in the perspective of dementia prevalence, demographic profile, per capita gross domestic product (GDP) and predominant healthcare financing model. The findings suggest that irrespective of the prevalence, country’s demographic profile, GDP per capita or the predominant financing model, dementia strategies primarily focus on “care”, implying the compliance of post-diagnostic support. Germany addresses almost all the fundamental rights of the Glasgow Declaration. Countries differ in their compliance with the key action areas of the WHO’s GAP, though post-diagnostic support is addressed by the dementia strategies across the clusters, whereas 3 out of 7 KAAs are not addressed by dementia strategies in any of the clusters.